The Effect of Parenting and Learning Processes on the Development of Children's Empathy - Barokah, Al; Badarussyamsi, Badarussyamsi (Green Publisher, 2023)
The effect of parenting and learning processes is a scientific literature review article. The purpose of writing this article is to build a hypothesis on the influence or role between variables that will be used in further research, within the scope of Islamic Education Management. The article writing method is the library research method, which is sourced from online media such as Google Scholar, PDF Drive and other academic online media. Qualitative descriptive analysis. The results of this article are: 1) Parenting has an effect on child empathy; 2) the learning process of children's empathy influences